The reliability and validity of ultrasound to quantify muscles in older adults: a systematic review. Issue 5 (12th July 2017) - Nijholt, Willemke; Scafoglieri, Aldo; Jager‐Wittenaar, Harriët; Hobbelen, Johannes S.M.; van der Schans, Cees P.
Abstract: This review evaluates the reliability and validity of ultrasound to quantify muscles in older adults. The databases PubMed, Cochrane, and Cumulative Index to Nursing and Allied Health Literature were systematically searched for studies. In 17 studies, the reliability ( n = 13) and validity ( n = 8) of ultrasound to quantify muscles in community‐dwelling older adults (≥60 years) or a clinical population were evaluated. Four out of 13 reliability studies investigated both intra‐rater and inter‐rater reliability. Intraclass correlation coefficient (ICC) scores for reliability ranged from −0.26 to 1.00. The highest ICC scores were found for the vastus lateralis, rectus femoris, upper arm anterior, and the trunk (ICC = 0.72 to 1.000). All included validity studies found ICC scores ranging from 0.92 to 0.999. Two studies describing the validity of ultrasound to predict lean body mass showed good validity as compared with dual‐energy X‐ray absorptiometry ( r 2 = 0.92 to 0.96). This systematic review shows that ultrasound is a reliable and valid tool for the assessment of muscle size in older adults. More high‐quality research is required to confirm these findings in both clinical and healthy populations. Furthermore, ultrasound assessment of small muscles needs further evaluation. Ultrasound to predict lean body mass is feasible; however, future research is required to validate prediction equations in older adults with varying function and health.